2022
DOI: 10.1080/22221751.2022.2030200
|View full text |Cite
|
Sign up to set email alerts
|

Homologous or heterologous booster of inactivated vaccine reduces SARS-CoV-2 Omicron variant escape from neutralizing antibodies

Abstract: The massive and rapid transmission of SARS-CoV-2 has led to the emergence of several viral variants of concern (VOCs), with the most recent one, B.1.1.529 (Omicron), which accumulated a large number of spike mutations, raising the specter that this newly identified variant may escape from the currently available vaccines and therapeutic antibodies. Using VSV-based pseudovirus, we found that Omicron variant is markedly resistant to neutralization of sera from convalescents or individuals vaccinated by two doses… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
117
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 122 publications
(127 citation statements)
references
References 39 publications
9
117
0
1
Order By: Relevance
“…Among the 15 RDB mutation, K417N (a mutation common with beta variant), and E484A are the mutations that lead to overwhelmingly disruptive effects to many known antibodies ( Chen et al, 2021a ). The sera from the individuals vaccinated by two doses of inactivated whole-virion vaccines (BBIBP-CorV) showed reduced neutralization by Omicron, however homologous or heterologous vaccination with protein subunit vaccine (ZF 2001) enhance neutralization against the Omicron ( Wang et al, 2022 ). Homologous boosting with BBIBP-CorV vaccine 9 months post two dose vaccination schedule in a cohort of 292 participants, revealed that in 78.08% participants Omicron got neutralized ( Yu et al, 2022 ).…”
Section: Booster Shots Of Vaccinesmentioning
confidence: 99%
“…Among the 15 RDB mutation, K417N (a mutation common with beta variant), and E484A are the mutations that lead to overwhelmingly disruptive effects to many known antibodies ( Chen et al, 2021a ). The sera from the individuals vaccinated by two doses of inactivated whole-virion vaccines (BBIBP-CorV) showed reduced neutralization by Omicron, however homologous or heterologous vaccination with protein subunit vaccine (ZF 2001) enhance neutralization against the Omicron ( Wang et al, 2022 ). Homologous boosting with BBIBP-CorV vaccine 9 months post two dose vaccination schedule in a cohort of 292 participants, revealed that in 78.08% participants Omicron got neutralized ( Yu et al, 2022 ).…”
Section: Booster Shots Of Vaccinesmentioning
confidence: 99%
“…The UK Health Security Agency (UKHSA) reports as well as other studies have also confirmed the descending vaccine effectiveness [ 42 , 43 ]. While further studies are needed, results from laboratory studies have suggested that the immunity resulting from a combination of vaccination and prior infection (hybrid immunity) or combined vaccination with different vaccine types (heterologous immunity) may offer some protection against the variant, which may be superior to vaccination with a single platform alone [ 44 , 45 ]. The Omicron variant, characterized by great immune evasion, escapes the majority of existing SARS-CoV-2 neutralizing antibodies [ 46 ].…”
Section: What Are the Causes Of Breakthrough Infections?mentioning
confidence: 99%
“…By 18 January 2022, a total of 9,571,502,663 vaccine doses had been administered [ 6 ]. However, scientific consensus is growing that current vaccines show relatively low neutralizing immunogenicity, no broad-spectrum efficacy, and little lasting protective immunity [ 8 ]. To address this grim outlook, the development of more effective, long-lasting and broad-spectrum vaccines is essential.…”
Section: Introductionmentioning
confidence: 99%